FORECASTING GROSS DOMESTIC PRODUCT (GDP) AND GDP GROWTH: AN EXPLORATION OF IMPROVED PREDICTION USING MACHINE LEARNING ALGORITHMS - Azibaev Akhmadkhon Gulomjon ugli (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article explores the significance of Gross Domestic Product (GDP) and GDP growth, the importance of accurate forecasting, and the role of machine learning algorithms in improving prediction accuracy. It reviews several studies that highlight the effectiveness of machine learning algorithms, such as random forest regression, linear regression, and autoregressive integrated moving average (ARIMA), in GDP forecasting. These algorithms analyze data, identify patterns, and make accurate forecasts, contributing to enhanced decision-making in economic analysis and planning.